(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
On the basis of the synthesized approach through a combination of institutional-evolutionary, behavioral methodology and synergetic approach the institutional nature of social capital is defined, which is constituted by informal (common values, rooted social norms and trust) and formal (network connections and models of social structure, its subinstitutions) role as a meta-institution, which is an effective mechanism for transforming the institutional architecture of economic systems and creating a favorable environment for the formation of new institutions and organizations that further define the goals, models, nature of economic development. The methodological bases of the analysis of the institution of social capital have been improved through complex measurement of its components and their interrelation with dynamics of macroeconomic indicators (GDP, the structure of state budget expenditures, the volume of internal investments, etc.) and indicators of entrepreneurship development (number and dynamics of business entities creation, business sector structure, the level of capitalization and socialization of business), allowing to optimize the methodology for assessing the economic potential of the institution of social capital and develop recommendations to increase the economic return from its use as a resource of the national economy. The determinants that condition the specifics of the productive use of the economic potential of the social capital institution in the national economy in the context of global transformations are systematized. The factors of deformation of the social capital institution in the national economy are revealed, which is a consequence of the previous trajectory of development and leads to the transformation of social capital into a predominantly extractive institution.